2020
DOI: 10.1007/s10592-020-01248-8
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of red deer (Cervus elaphus) administrative management units in a human-dominated landscape

Abstract: Red deer (Cervus elaphus) throughout central Europe are influenced by different anthropogenic activities including habitat fragmentation, selective hunting and translocations. This has substantial impacts on genetic diversity and the long-term conservation of local populations of this species. Here we use genetic samples from 480 red deer individuals to assess genetic diversity and differentiation of the 12 administrative management units located in Schleswig Holstein, the northernmost federal state in Germany… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 78 publications
(93 reference statements)
3
17
0
Order By: Relevance
“…Heightened road densities in urban environments present a salient environmental challenge that can restrict successful colonization of viable urban habitats. Though taxa from multiple clades are affected, mortality risks are especially high for large vertebrates within cities (Edelhoff et al., 2020; Honda et al., 2018; Johnson et al., 2020) and at the urban–wildland interface (Proctor et al., 2020; St. Clair et al., 2019; Wynn‐Grant et al., 2018), where human‐modified attributes of the landscape and speed limits increase (Neumann et al., 2012). All these factors contribute to the reduced occupancy and population abundances of larger fauna in urban systems.…”
Section: Ecological Drivers Of Conflict and Associated Biological Outmentioning
confidence: 99%
“…Heightened road densities in urban environments present a salient environmental challenge that can restrict successful colonization of viable urban habitats. Though taxa from multiple clades are affected, mortality risks are especially high for large vertebrates within cities (Edelhoff et al., 2020; Honda et al., 2018; Johnson et al., 2020) and at the urban–wildland interface (Proctor et al., 2020; St. Clair et al., 2019; Wynn‐Grant et al., 2018), where human‐modified attributes of the landscape and speed limits increase (Neumann et al., 2012). All these factors contribute to the reduced occupancy and population abundances of larger fauna in urban systems.…”
Section: Ecological Drivers Of Conflict and Associated Biological Outmentioning
confidence: 99%
“…In absolute terms however, the data of the Hessian population show rather favourable heterozygosity and lower Fis values in comparison with other national (Poetsch et al 2001;Kuehn et al 2003;Zachos et al 2007;Edelhoff et al 2020) and international studies (Hmwe et al 2006a, b;Nussey et al 2007;Nielsen et al 2008;Sanchez-Fernandez et al 2008;Zsolnai et al 2009). The lowest heterozygosity and the highest F values are typically found in small islet populations and populations with longer history of isolation and low population sizes (Hmwe et al 2006a, b;Hajji et al 2008;Zachos and Hartl 2011;Zachos et al 2016;Edelhoff et al 2020). However, it must be taken into account that both measures are decisively influenced by the markers used, their number, and the sample size (Reiner et al 2019).…”
Section: Discussionmentioning
confidence: 77%
“…However, Jost's D also achieves a maximum of 0.24 for an area comparison (KF to OD), which realistically no longer permits any genetic exchange due to the intervening traffic and settlement areas (Rhine-Main metropole, several fenced motorways). A comparison with Jost's D values from Schleswig-Holstein (Edelhoff et al 2020) showed 87% higher values for the Hessian areas. Despite the lack of absolute comparability, this at least indicates an even greater differentiation in Hesse than in the clearly isolated areas of Schleswig-Holstein that are marked by inbreeding depressions (Zachos et al 2007).…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations